2020
DOI: 10.3390/sym12071177
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Considerations and Study of the Fractal Dimension around the Posterior Superior Alveolar Artery

Abstract: The Posterior Superior Alveolar Artery (PSAA) provides vascular support to molars, gingiva, and maxillary sinus. A tear of the PSAA may cause profuse hemorrhages which may lead to complications at a surgical level. As such, it becomes crucial to anatomically analyse several features regarding the PSAA as well as the area surrounding it. In this paper, we are particularly interested in the study of the complexity of the periodontal tissue structure which appears close to the location of the PSAA. A total amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…These included studies utilizing radiographs other than CBCT, 22 42 43 44 45 46 47 48 49 50 51 studies with internal inconsistencies related to their reported results 52 53 , those that did not investigate the PSAA as a whole unit (for instance, only analyzing a branch of the PSAA), 36 54 55 56 57 58 and those that did not analyze at least 1 PSAA characteristic pertinent to the present inclusion criteria. 59 60 …”
Section: Resultsmentioning
confidence: 99%
“…These included studies utilizing radiographs other than CBCT, 22 42 43 44 45 46 47 48 49 50 51 studies with internal inconsistencies related to their reported results 52 53 , those that did not investigate the PSAA as a whole unit (for instance, only analyzing a branch of the PSAA), 36 54 55 56 57 58 and those that did not analyze at least 1 PSAA characteristic pertinent to the present inclusion criteria. 59 60 …”
Section: Resultsmentioning
confidence: 99%